2006
DOI: 10.1002/ptr.1937
|View full text |Cite
|
Sign up to set email alerts
|

Effect of piperine on the steady‐state pharmacokinetics of phenytoin in patients with epilepsy

Abstract: Piperine, the active principle of Piper longum, Piper nigrum and Zingiber officinalis, has been reported to enhance the oral bioavailability of phenytoin in human volunteers. The objective of this study was to explore the effect of a single dose of piperine in patients with uncontrolled epilepsy on the steady-state pharmacokinetics of phenytoin. Two groups of 10 patients each receiving either a 150 mg or 200 mg twice daily dose of phenytoin were selected. Twelve hours after the night dose, venous blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 6 publications
1
42
1
Order By: Relevance
“…[40][41][42][43][44] In our study, the "area-under-the-curve" (AUC) of 11 increased following in vivo administration of the extract, suggesting that the other constituents in the extract inhibit the metabolism of 11. 19) Previous studies have demonstrated that flavonoids and/or flavonoid-rich fractions ameliorate experimental diabetes in mice and rats.…”
Section: Retrofractamide a And Related Compounds From The Fruit Of Pimentioning
confidence: 88%
“…[40][41][42][43][44] In our study, the "area-under-the-curve" (AUC) of 11 increased following in vivo administration of the extract, suggesting that the other constituents in the extract inhibit the metabolism of 11. 19) Previous studies have demonstrated that flavonoids and/or flavonoid-rich fractions ameliorate experimental diabetes in mice and rats.…”
Section: Retrofractamide a And Related Compounds From The Fruit Of Pimentioning
confidence: 88%
“…The piperine is one of the most well-known components because of its high medicinal properties (Bhardwaj et al, 2002;Gao & Morozowich, 2006). In Indian medicine, the piperine and its derivatives were always used for treating epilepsy, headache and so on (Pattanaik et al, 2006). As increasingly popular modern-day uses of piperine, it has been reported to inhibit oxidative stress, antifungal, anti-inflammatory activity and anti-tumor (Sunila & Kuttan, 2004;Bezerra et al, 2008;Ee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…has been shown to be effective as a bioavailability enhancer of several drugs and other pharmacologically active substances (phenytoin, propranolol, theophylline, nevirapine, beta-lactam antibiotics, curcumin, coenzyme Q10, and epigallocatechin) in animals and human volunteers [1][2][3][4][5][6][7]. Recently a novel series of substituted piperine analogues have been synthesized in our laboratory [8], for the purpose of identifying potential leads as bioenhancer(s) for anti-cancer agents, majority of which exhibit low/variable oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%